Insights into the molecular mechanisms of aging and caloric restriction : the potential of three putative life-extending drugs in the nematode "Caenorhabditis elegans" - Ferreira, Fábio Júnio Veríssimo (2014)
Dissertação de mestrado em Genética Molecular